Think Twice: Effects on Diagnostic Accuracy of Returning to the Case to Reflect Upon the Initial Diagnosis. (August 2020) - Mamede, Sílvia; Hautz, Wolf E.; Berendonk, Christoph; Hautz, Stefanie C.; Sauter, Thomas C.; Rotgans, Jerome; Zwaan, Laura; Schmidt, Henk G.
Abstract : Purpose: Diagnostic errors have been attributed to failure to sufficiently reflect on initial diagnoses. However, evidence of the benefits of reflection is conflicting. This study examined whether reflection upon initial diagnoses on difficult cases improved diagnostic accuracy and whether reflection triggered by confrontation with case evidence was more beneficial than simply revising initial diagnoses. Method: Participants were physicians in Bern, Switzerland, registered for the 2018 Swiss internal medicine certification exam. They diagnosed written clinical cases, providing an initial diagnosis by following the same instructions and returning to the case to provide a final diagnosis. The latter required different types of reflection depending on the physician's experimental condition: return without instructions, identify confirmatory evidence, identify contradictory evidence, or identify both confirmatory and contradictory evidence. The authors examined diagnostic accuracy scores (range 0–1) as a function of diagnostic phase and reflection type. Results: One hundred and sixty-seven physicians participated. Diagnostic accuracy scores did not significantly differ between the 4 groups of physicians in the initial (I) or the final (F) diagnostic phase (mean [95% CI]: return without instructions, I: 0.21 [0.17, 0.26], F: 0.23 [0.18, 0.28]; confirmatory evidence, I: 0.24 [0.19, 0.29], F: 0.31 [0.25, 0.37]; contradictory evidence, I: 0.22 [0.17, 0.26], F: 0.26 [0.22, 0.30]; confirmatory and contradictory evidence, I: 0.19 [0.15, 0.23], F: 0.25 [0.20, 0.31]). Regardless of type of reflection employed while revising the case, accuracy increased significantly between initial and final diagnosis, I: 0.22 (0.19, 0.24) vs F: 0.26 (0.24, 0.29); P < .001. Conclusions: Physicians' diagnostic accuracy improved after reflecting upon initial diagnoses provided for difficult cases, independently of the evidence searched for while reflecting. The findings support the importance attributed to reflection in clinical teaching. Future research should investigate whether revising the case can become more beneficial by triggering additional reflection. Abstract : Supplemental Digital Content is available in the text.